Influence of the physicochemical characteristics of mosquito breeding sites in domestic environments on the distributions of Anopheles, Aedes and Culex mosquitoes in Benin - Isidore Hoyochi; Germain Gil Padonou; Tatchémè Filémon Tokponnon; Alphonse Keller Konkon; David Mahouton Zoungbédji; Albert Sourou Salako; Brice Dangnon; A. Virgile Onésime Akowanou; Luc Olivier Sintondji; Edmond Sossoukpe; Lamine Baba-Moussa; Martin Codjo Akogbéto (Tropical Medicine and Health)
Abstract Background Malaria, dengue and lymphatic filariasis are diseases transmitted by Anopheles, Aedes and Culex mosquitoes, respectively. These mosquitoes have evolved and adapted to environmental conditions and human lifestyles, providing them with a variety of breeding sites. This study aimed to determine the influence of the physicochemical characteristics of breeding sites on the distribution of Anopheles, Aedes and Culex mosquitoes in Benin. Methods The collections took place from January to November 2025 and lasted 9 months. Mosquito larvae were collected from 11 municipalities in Benin. Physicochemical parameters such as pH, temperature, salinity, total dissolved solids, conductivity, dissolved oxygen and turbidity were measured in situ during larval sampling. Variations among the physicochemical parameters were assessed via Chi-square multiple comparisons of proportions and the least significant difference (LSD) test following analysis of variance (ANOVA). Correlations between physicochemical variables were analyzed via principal component analysis (PCA). Results The results revealed that domestic containers and tires were the most common indoor and outdoor breeding sites for human dwellings, respectively. The pH levels slightly varied across the different breeding sites but generally remained nearly neutral. The temperatures were relatively consistent among the habitats, averaging approximately 30 °C. Salinity levels were close to zero at most Aedes and Anopheles breeding sites, whereas Culex larvae were commonly associated with sites with salinity values close to one. The total dissolved solids and conductivity varied considerably among the sites. Dissolved oxygen was positively correlated with the presence of Anopheles larvae. Both Aedes and Anopheles are typically found in habitats with low turbidity, whereas Culex larvae are associated with highly turbid environments, with turbidity ranging from 10 to 858 NTU. Principal component analysis revealed strong positive correlations between conductivity, salinity, and TDS; weak correlations between turbidity and temperature; and negative correlations between dissolved oxygen, conductivity, and salinity. Conclusion This study highlights the importance of the physicochemical properties of breeding sites in the distribution of primary vector mosquito species. The prevalence of domestic containers and tires as breeding sites underscores the necessity of targeted interventions in these habitats, both indoors and outdoors of human dwellings.